Tinjauan Hukum Islam terhadap Pembentukan Keluarga Sakinah pada Prajurit TNI di Batalyon Infanteri 403/Wirasada Pratista Yogyakarta - Najih Abqori (Indonesia, 2020)
This study examines the consideration of forming a sakinah family, Every TNI family in Infantry Battalion 403 / WP had their respective efforts in forming a sakinah family. In these efforts there are various obstacles, such as when a husband is assigned to a certain area for a period of six months to one year and the wife must be in the dormitory. Given this phenomenon, the authors are interested in researching and knowing more about the efforts in forming a sakinah family and reviewing these efforts with a review of Islamic law. This type of research is field research using qualitative data analysis. This research is a descriptive analysis, while the data collection used is observation and interviews. The approach used is normative-juridical. Based on the research that the author did, the efforts made are: First, maintaining good communication. Second, be honest, trust each other, look after each other, teach courtesy, respect each other and remind each other. Third, apply the principle of deliberation. Fourth, teach religious education. The environment in the Yonif 403 / WP military dormitory can have an effect, but not all of it, is the main reason for forming a sakinah family, because a sakinah family is a goal to be achieved by each family.